2015
DOI: 10.1007/12_2015_327
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nucleation of Crystalline Phases Within Homopolymers, Polymer Blends, Copolymers, and Nanocomposites

Abstract: Self-nucleation (SN) is a special nucleation process triggered by selfseeds or self-nuclei that are generated in a given polymeric material by specific thermal protocols or by inducing chain orientation in the molten or partially molten state. SN increases the nucleation density of polymers by several orders of magnitude, producing significant modifications to their morphology and overall crystallization kinetics. In fact, SN can be used as a tool for investigating the overall isothermal crystallization kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
325
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(337 citation statements)
references
References 179 publications
(188 reference statements)
12
325
0
Order By: Relevance
“…With this aim, a standard self‐nucleation procedure was followed. The standard crystalline state was created by annealing the sample at 140 °C (or 120 °C for Form I seeded samples) for 3 min before cooling to 30 °C at 10 °C min −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With this aim, a standard self‐nucleation procedure was followed. The standard crystalline state was created by annealing the sample at 140 °C (or 120 °C for Form I seeded samples) for 3 min before cooling to 30 °C at 10 °C min −1 .…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, the sample was heated to a selected self‐nucleation temperature (holding time of 5 min), and the subsequent crystallization temperature upon cooling at 10 °C min −1 was recorded. An extensive description of the self‐nucleation thermal protocol can be found elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, often in industrial settings, external nucleating agents are added to decrease the nucleation barrier in order to accelerate crystallization. It has also been demonstrated that self‐nucleation can be highly effective in increasing crystallization rate . The number of nuclei induced by self‐nucleation can overcome, by several orders of magnitude, the number of commonly found heterogeneous nuclei in a bulk polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The melting of crystals at low temperatures near T g retains nuclei that can enhance cold-crystallization. For high melting temperatures such nucleus retention has in the past been called selfnucleation and the nuclei were found to survive heating above the equilibrium melting temperature [226][227][228][229][230][231]. This research has, thus, opened a new direction of inquiry to gather quantitative information about nucleation and growth of polymer crystals as it affects the amorphous and crystalline phases and their interrelationship.…”
Section: Discussionmentioning
confidence: 99%